Behavior of Adult Aedes aegypti and Aedes albopictus in Kinshasa, DRC, and the Implications for Control - Emile Zola Manzambi; Guillaume Binene Mbuka; Gillon Ilombe; Richard Mundeke Takasongo; Francis Wat’senga Tezzo; Maria del Carmen Marquetti; Emery Metelo; Veerle Vanlerberghe; Wim Van Bortel (Tropical Medicine and Infectious Disease, 2023)
Yellow fever and chikungunya outbreaks—and a few dengue cases—have been reported in the Democratic Republic of the Congo (DRC) in recent years. However, little is known about the ecology and behavior of the adult disease vector species, Aedes aegypti and Aedes albopictus, in DRC. Preliminary studies showed important differences in Aedes behavior in DRC and Latin-American sites. Therefore, this study aimed to assess the host-seeking and resting behaviors of female Ae. aegypti and Ae. albopictus, and their densities in four communes of Kinshasa (Kalamu, Lingwala, Mont Ngafula and Ndjili). Two cross-sectional surveys were carried out, one in the dry season (July 2019) and one in the rainy season (February 2020). We used three different adult vector collection methods: BG-Sentinel 2, BG-GAT, and prokopack. Both Aedes species were clearly exophagic, exophilic, and sought breeding sites outdoors. The adult house index for Ae. aegypti exceeded 55% in all communes except Lingwala, where it was only 27%. The Adult Breteau Index (ABI) for Ae. aegypti was 190.77 mosquitoes per 100 houses inspected in the rainy season and 6.03 in the dry season. For Ae. albopictus, the ABI was 11.79 and 3.52 in the rainy and dry seasons, respectively. Aedes aegypti showed unimodal host-seeking activity between 6 h and 21 h. The exophagic and exophilic behaviors of both species point to the need to target adult mosquitoes outdoors when implementing vector control.